FAKTOR YANG MEMPENGARUHI RESPON AUDITOR DALAM MENDETEKSI SALAH SAJI MATERIAL SEBAGAI AKIBAT FRAUDULENT FINANCIAL STATEMENT (STUDI PADA KANTOR AKUNTAN PUBLIK DI SEMARANG) - Fakhri Ashrial Yusnar; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
This study aims to obtain empirical evidence of factors that affect fraudulent financial statements using fraud triangle perspective. This study is the development of several previous studies, in context testing independent variables contained in the fraud triangle, such as the pressure, opportunity, attitude, and also culture as an additional variable to indicate the fraud. This study uses primary data obtained directly from respondents. To obtain important information from the respondents, then use of purposive sampling technique. Data obtained by distributing questionnaires to 52 auditors who work in public accounting firm in the city of Semarang, Indonesia. Statistical analysis method used is multiple linear regressions. Hypothesis testing is done with the help of software IBM SPSS Statistics 20. The results of this study indicate that: first, effect of individual pressures as a less incentive from the company will improve respond auditors in detecting fraudulent financial statement. Second, opportunities for cheating high will improve the response of auditors in detecting fraudulent financial statement. Third, highly attitude of the company about fraud will increase the response auditors in detecting the fraudulent financial statement and worse corporate culture will improve the response auditors in detecting fraudulent financial statement.  It can be concluded that the entire hypothesis is accepted.